Employer Branding and Career Opportunities: Does Fit really influence Gen Z’s intention to join in architectural firms in Indonesia? - Soraya, Altheannisa Agatha (Syntax Corporation, 2024)
By the end of the Covid-19 pandemic, job demand has increased. Indonesian Architecture subsector is experiencing a shortage of architects given the lack of interest on architecture students to continue their careers in the same field and lack of career opportunities offered. Therefore, employers need to develop an employer branding strategy to match applicant’s expectations with values offered in order to attract labor market intention, especially alumnis from related majors, to join architectural company. As Person-Organisation Fit theory applied, by finding their fit toward potential employee, gen Z, can better examine their employer to consider joining the company. This study aims to examine how person-organisation fit mediates career growth opportunities and employer branding that fit individual’s expectations can influence their intention to join to the company. This quantitative research uses a cross-sectional approach by collecting data through structured questionnaire consisting of 41 items asked distributed online. The sample consisted of 308 employees working in architectural industry with minimum of one year experience. Covariance Based Structural Equation Modeling (CB-SEM) used as analysis method aimed to identify and analyze the relationship between variables that influence the gen Z’s intention to join Indonesian architecture firms. The eresults indicates that both Employer Branding and Career Growth Opportuniies hav positive and significant effect on Intention to Join, while Person-Organisation fit partially mediate Employer Branding’s effect. This study only conducted in Architectural Subsector in Indonesia. The results of this study could also have relevance for other Asian nations that exhibit comparable traits.